Acute Genital Ulcers in a Woman Secondary to COVID-19 Infection: A Case Report - Zhang J; Wang D; Chen M; Li J; Huang W (Dove Medical Press, 2024)
Jia Zhang,1,* Danni Wang,1,* Mingjing Chen,1 Jiajun Li,2 Wenxiang Huang1 1Department of Geriatrics, the First Affiliated Hospital of Chongqing Medical University, Chongqing, People's Republic of China; 2Department of Infectious Diseases, the First Affiliated Hospital of Chongqing Medical University, Chongqing, People's Republic of China*These authors contributed equally to this workCorrespondence: Wenxiang Huang, Department of Geriatrics, the First Affiliated Hospital of Chongqing Medical University, Chongqing, People's Republic of China, Tel +86 13883533808, Email wenxiang_huang@163.comAbstract: Acute genital ulcers (AGU) have been associated with various pathogens, such as Epstein-Barr virus (EBV) and cytomegalovirus (CMV). However, cases of AGU associated with coronavirus disease 2019 (COVID-19) are rare, and this disease significantly impairs human quality of life. In this case, we report a 37-year-old woman who presented with a five-day history of a painful genital ulcer and fever. A month earlier, she had experienced a COVID-19 infection that resolved without medical therapy. Physical examination revealed that multiple asymmetric ulcers presented on labia minora covered with whitish exudates. The patient, without any high-risk sexual behavior, or a personal or family history of autoimmune disorders or inflammatory bowel disease, was diagnosed with COVID-19-related AGU after ruling out other infectious and immune diseases. Following a two-week treatment of oral prednisone, her vulvar edema, ulcers, and fever improved significantly. This case suggests that AGU may be triggered by a COVID-19 infection.Keywords: COVID-19, SARS-CoV-2, acute genital ulcers, fever